Prevalence and associated factors of airway hyper- responsiveness in children with recurrent chronic cough - I Gusti Agung Ngurah Sugitha Adnyana; Putu Suwendra; Hendra Santoso (Paediatrica Indonesiana, 2004)
Background Airway hyper-responsiveness (AH) is a common char-acteristic of asthma. Patient who has recurrent chronic cough withAH is commonly referred as â€œcough variant asthmaâ€. Histamineprovocation test should be performed to determine whether a pa-tient has â€œcough variant asthmaâ€ or recurrent viral bronchitis.Objective To determine AH prevalence in children with recurrentchronic cough and factors associated with it.Methods A cross sectional study was conducted on 6-12 year-oldchildren with recurrent chronic cough at the Pediatrics OutpatientClinic, Sanglah Hospital Denpasar from September 2002 until June2003Results Twenty one out of 64 (33%) subjects suffering from recur-rent chronic cough without wheezing had AH. Associated factorssignificantly associated with AH were age, allergic rhinitis, pater-nal and maternal history of atopy, passive smoking, use of mos-quito-coil, positive skin prick test, and eosinophilia. Spearman cor-relation analysis between associated factors and AH showed thatpositive skin prick test and passive smoking were moderately cor-related with AH (r=0.56, p<0.0001; r=0.57, p<0.0001, respectively),whereas multivariate regression logistic analysis on associatedfactors found true associated factors, such as positive skin pricktest (p=0.01; OR=14.82), history of atopy in father (p=0.02;OR=22.75), and passive smoking (p=0.03; OR=11.97).Conclusions The prevalence of airway hyper-responsiveness inchildren with recurrent chronic cough without history of wheezingwas 33%. Independent associated factors of AH in recurrent chroniccough children are positive skin prick test, history of atopy in fa-ther, and passive smoking